An investigation into the role of 2, 6-lutidine as an additive for the RuCl3-NaIO4 mediated oxidative cleavage of olefins to ketones. Issue 51 (19th December 2018) - Watson, David W.; Gill, Matthew; Kemmitt, Paul; Lamont, Scott G.; Popescu, Mihai V.; Simpson, Iain
Graphical abstract: Highlights: 2, 6-Lutidine used as a beneficial additive for the oxidation of olefins to ketones. The oxidative system uses NaIO4 in the presence of catalytic RuCl3 . Shortened reaction times and improved yields observed. A range of functional groups are tolerated. Abstract: 2, 6-Lutidine has been identified as a beneficial additive for the oxidative cleavage of olefins to ketones by NaIO4 in the presence of catalytic RuCl3, improving the yield and shortening the reaction times. In the absence of 2, 6-lutidine reactions stalled at the diol intermediate with incomplete conversion to the desired ketones. The reaction protocol described herein also avoids the use of harmful solvents such as CCl4 and DCE and is tolerant of a range of functional groups.